Fiscal policy in the EU countries most affected by the crisis: Greece, Ireland, Portugal, and Spain - Anna Krajewska (Comparative Economic Research. Central and Eastern Europe, 2014)
The global financial crisis which began in 2007-2008 had a negative effect on the economy of the European Union, mainly in selected countries of the euro area: Greece, Ireland, Portugal and Spain. These peripheral euro zone countries come out of recession and the financial crisis largely due to the great financial support of the international institutions. Hundreds of billions of euro were spent to save these economies. At the same time, however, these countries were characterized by the lowest level of fiscal policy - measured by share of taxes in GDP - among the countries of the euro area. In this paper I will try to answer the following questions: 1. What were the causes of the downturn in those countries, and what restructuring actions were taken; 2. What changes were introduced in the tax system under the policy to repair public finances; 3. How have these changes affected the level and the structure of budget revenues from taxes, and to what extent has the crisis affected the change in the tax burden on consumption, labour, and capital.
Keywords: 330; taxes; financial crisis; Greece; Portugal; Spain; Ireland